2012
DOI: 10.4161/auto.20069
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the starvation-induced gene Rack1 leads to glycogen deficiency and impaired autophagic responses in Drosophila

Abstract: Autophagy delivers cytoplasmic material for lysosomal degradation in eukaryotic cells. Starvation induces high levels of autophagy to promote survival in the lack of nutrients. We compared genome-wide transcriptional profiles of fed and starved control, autophagy-deficient Atg7 and Atg1 null mutant Drosophila larvae to search for novel regulators of autophagy. Genes involved in catabolic processes including autophagy were transcriptionally upregulated in all cases. We also detected repression of genes involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 55 publications
6
51
1
Order By: Relevance
“…Drosophila Rack1, a receptor of activated protein kinase C 1, increases 4.1-to 5.5-fold during nutrient deprivation in all three genotypes. Recently, it was reported that loss of Rack1 led to an attenuated autophagic response to starvation [22] . This starvationinduced protein potentially acts as a scaffold protein during autophagosome formation.…”
Section: Starvation Inducersmentioning
confidence: 99%
“…Drosophila Rack1, a receptor of activated protein kinase C 1, increases 4.1-to 5.5-fold during nutrient deprivation in all three genotypes. Recently, it was reported that loss of Rack1 led to an attenuated autophagic response to starvation [22] . This starvationinduced protein potentially acts as a scaffold protein during autophagosome formation.…”
Section: Starvation Inducersmentioning
confidence: 99%
“…RACK1 Interacts with LC3-It was reported that loss of RACK1 resulted in attenuated autophagy and glycogen store in Drosophila, and RACK1 was partially colocalized with the Drosophila LC3 homolog Atg8 (27). We observed that RACK1 interacted with LC3 with endogenous or exogenously FIGURE 3.…”
Section: Rack1 Inhibits Dvl-mediated Wntmentioning
confidence: 56%
“…In fact, involvement of RACK1 was suggested in Drosophila studies where loss of RACK1 was associated with attenuated autophagy responses and glycogen storage defects (14). While our manuscript was in preparation, Zhao et al (15) showed that RACK1 was required for hepatocyte autophagy and lipophagy.…”
Section: Discussionmentioning
confidence: 69%
“…Recent studies showed that WD domain-containing proteins, such as ATG16L1, ALFY, and WIPI1, play significant roles in different stages of the autophagy pathway (12)(13)(14)(15)(16). In this study, we describe RACK1 (receptor-activated C-kinase 1, GNB2L1), a WD40 repeat protein with a seven-bladed ␤-propeller structure, as an interaction partner of ATG5 and a novel autophagy protein.…”
mentioning
confidence: 90%